Microscopic Flow Characteristics of Fluids in Porous Medium and Its Relationship with Remaining Oil Distribution: A Case Study in Saertu Oilfield of Daqing in China - Z. Li; X. Sun; F. Wang; Y. Liang (Geofluids)
The Saertu Oilfield of Daqing in northeast China has entered ultrahigh water-cut stage of development. Numerical simulation is applied in this paper to study characteristics of microscopic fluid velocity and flow pressures variation in the core pores in the Beier Area of Saertu Oilfield. The relationship between the remaining oil distribution and microscopic flow characteristics of fluid in the pores has been analyzed. Study results show that, in the reservoir with stronger heterogeneity of grain size and throat (corresponding to high coordinate number), high flow velocities tend to occur in relatively wider pore throats with great differentiation of flow velocities. The dominant passages are developed in high capacity channel, the detour flows are created in large porous channels, and the isolated islands are formed in small porous channels. The flow velocity declines slowly with long duration of high pressure. Few pores are swept by injected fluids with low sweep efficiency. The microscopic remaining oil is mainly distributed in cluster state. The content of remaining oil is higher with lower oil displacement efficiency. By contrast, in the reservoir with weaker heterogeneity of grain size and throat (corresponding to low coordinate number), high flow velocities also develop in relatively narrower pore throats with little differentiation of flow velocities. The development of detour flows is weaker in large porous channels. The flow velocity declines quickly with a short duration of high pressure. More pores are swept by fluids with high sweep efficiency. The remaining oil is mainly distributed in state of thin film on pore surface. The content of remaining oil is lower with higher oil displacement efficiency.